Genetic Variants and Immune Responses in a Cohort of Patients With Varicella Zoster Virus Encephalitis. (11th May 2021) - Thomsen, Michelle M; Tyrberg, Tobias; Skaalum, Kristoffer; Carter-Timofte, Madalina; Freytag, Mette R; Norberg, Peter; Helleberg, Marie; Storgaard, Merete; Nielsen, Henrik; Bodilsen, Jacob; Grahn, Anna; Mogensen, Trine H
Abstract: Background: Infection with varicella zoster virus (VZV) may involve different central nervous system (CNS) manifestations, including meningitis, encephalitis, and vasculitis. In cases in which otherwise healthy individuals are affected, an inborn error of immunity may underlie increased susceptibility or severity of infection. Methods: We collected a cohort of 17 adults who experienced VZV encephalitis and performed whole exome sequencing. Patient peripheral blood mononuclear cells were infected with VZV, and innate antiviral interferon (IFN) and cytokine responses as well as viral replication were evaluated. Data were analyzed by Mann-Whitney U test. Results: We identified a total of 21 different potentially disease-causing variants in a total of 13 of the 17 patients included. These gene variants were within 2 major functional clusters: (1) innate viral sensors and immune pathways and (2) autophagy pathways. Antiviral IFN and cytokine responses were abnormal in the majority of patients, whereas viral replication was increased in only 2 of 17 patients. Conclusions: This study identifies a list of variants of pathogenic potential, which may serve as a platform for generating hypotheses for future studies addressing genetic and immunological factors associated with susceptibility to VZV encephalitis. These data, taken together, suggest that disturbances in innate sensing and autophagy pathways may predispose to VZV encephalitis. Abstract : This study identifies genetic variants of pathogenic potential and explores innate interferon and cytokine responses to VZV infection in VZV encephalitis patients. These data suggest that disturbances in innate sensing and autophagy pathways may predispose to VZV encephalitis.